Factors in economic development - Cairncross, Alec (London : Allen & Unwin, 1962)
The book contains twenty lectures and papers presented in the past decade (1952-1962. It discloses the intimate knowledge and imaginative perception of the broad spectrum of contemporary economic problems that its distinguished author possesses. The scope of his investigations embraces the fields of international trade, economic history, and economic growth. However, the principal focus is on the economic dilemmas and the non-economic constraints which confront the relatively underdeveloped nations as they strive to improve their standard of living.
Includes bibliographical references.
lje 24/01/2018
Loans
Keywords: Economic development